2018
DOI: 10.4172/2472-4971.1000162
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel, Diagnostic microRNA Signature in Papillary Thyroid Cancer

Abstract: Diagnosis is based on ultrasound and fine needle aspiration pathological findings. Screening asymptomatic people as well as those being at normal risk for thyroid cancer is not recommended. "Molecular signatures" consisting of miRNAs could be accounted for as promising diagnostic and/or prognostic biomarkers for different human malignancies, including thyroid cancer. MicroRNA molecules, being stable in blood and urine, are ideal components of molecular signatures. In this study, we sought to identify a molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However the deregulation of several identified miRNAs in this study has previously been well confirmed in PTC (bold fonts in Table 5). Among previously reported deregulated miRNAs, the upregulation of hsa-miR-146b and hsa-miR-222 and the down-regulation of hsa-miR-144 have been also reported in the blood of PTC patients (Poulios et al, 2018, Yu et al, 2012. A similar comparison to that of mRNAs was also carried out for differential expressed miRNAs to identify further deregulation of their expression in higher stages.…”
Section: Results Mrnas and Mirnas Deregulationsmentioning
confidence: 93%
“…However the deregulation of several identified miRNAs in this study has previously been well confirmed in PTC (bold fonts in Table 5). Among previously reported deregulated miRNAs, the upregulation of hsa-miR-146b and hsa-miR-222 and the down-regulation of hsa-miR-144 have been also reported in the blood of PTC patients (Poulios et al, 2018, Yu et al, 2012. A similar comparison to that of mRNAs was also carried out for differential expressed miRNAs to identify further deregulation of their expression in higher stages.…”
Section: Results Mrnas and Mirnas Deregulationsmentioning
confidence: 93%
“…However the deregulation of several identified miRNAs in this study has previously been well confirmed in PTC (bold fonts in Table 5). Among previously reported deregulated miRNAs, the upregulation of hsa-miR-146b and hsa-miR-222 and the down-regulation of hsa-miR-144 have been also reported in the blood of PTC patients [21,22]. A similar comparison to that of mRNAs was also carried out for differential expressed miRNAs to identify further deregulation of their expression in higher stages.…”
Section: Mirnamentioning
confidence: 88%